The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/archdischild-2020-319291
|View full text |Cite
|
Sign up to set email alerts
|

Provider visual attention on a respiratory function monitor during neonatal resuscitation

Heidi Herrick,
Danielle Weinberg,
Charlotte Cecarelli
et al.

Abstract: BackgroundA respiratory function monitor (RFM) provides real-time positive pressure ventilation feedback. Whether providers use RFM during neonatal resuscitation is unknown.MethodsAncillary study to the MONITOR(NCT03256578) randomised controlled trial. Neonatal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
(8 reference statements)
0
9
3
Order By: Relevance
“…2) and away from the manikin consistent with former studies. 31,32 However, this shift in attention was not harmful to performance in our study. We further observed that more experienced participants spent more time looking at the feedback device than on the manikin.…”
Section: Discussioncontrasting
confidence: 54%
“…2) and away from the manikin consistent with former studies. 31,32 However, this shift in attention was not harmful to performance in our study. We further observed that more experienced participants spent more time looking at the feedback device than on the manikin.…”
Section: Discussioncontrasting
confidence: 54%
“…In a sub-study of this trial, caregivers at two participating centres wore an eye-tracking equipment during the resuscitation, which demonstrated that caregivers did frequently look at the RFM. 18 Unfortunately, this study does not inform us on which RFM variables caregivers focused. It is possible that caregivers saw the RFM data, but familiar parameters, such as chest rise, SpO 2 and HR, were given greater consideration in decisions regarding PPV.…”
Section: Discussionmentioning
confidence: 92%
“…These studies should assess long-term neurodevelopmental outcomes. Studies are also required to determine whether an RFM adds to the attentional and cognitive demands on healthcare providers or diverts attention away from the infant 40–44. It is unclear whether specialised training is required to maximise the benefit of an RFM 43…”
Section: Discussionmentioning
confidence: 99%